Temporal-spatial variation atlas analysis of land use: A case study from Yiyang City, Hunan Province, China. (October 2019) - Xue, Yun; Tang, Fanghua; Liu, Shishi; Liu, Jianglong; Sun, Yurong
Abstract: The paper finished the land use time series changes atlas analysis, spatial series changes atlas analysis and the fluctuation potential map analysis of Yiyang city by using the land use data in 2005, 2010 and 2014. The results show that: (1) during the period from 2005 to 2014, the land use situation in Yiyang changed greatly, the area of construction land and water continued to increase, the garden area was decreasing, the area of cultivated land increased first and then decreased, meanwhile the area of woodland first decreased and then increased, and the area of cultivated land and woodland decreased as a whole. In the newly added area, the cultivated area rose the strongest, followed by woodland and water. In the shrinking area, the woodland area decreased most significantly, followed by cultivated land and the construction land area transfer rate was relatively low. (2) On the land use change amplitude and velocity view, the most obvious growth type of land use in Yiyang is construction land, and the scale of construction land expansion in Anhua County is relatively large. Then followed by water area, in which the maximum growth rate is in Heshan District and the next is in Anhua County. The other types of land use were all reduced.(3) From the analysis of relative change rate of land use type, the regional difference of land use type change in Yiyang is remarkable. In the last ten years, the biggest increasing range of construction land and cultivated land is in Anhua County relative to the whole city, and the biggest garden land increasing rate appears in Nanxian County. There is relatively great difference in forest land increasing rate, the biggest rate appears in Ziyang District, The difference in relative rates of change in waters is small, except the Heshan District and Anhua County have relative large variations, the changes in other parts of water with the relatively consistent.